An unusual case of bowel perforation - Lazarescu, Roxana Elena (BMJ Publishing Group, 2014)
Bowel perforation is a potentially fatal complication of obstruction, ischaemia, trauma, surgery and medications. It is recognised by clinical suspicion based on history, symptoms of severe abdominal pain and signs such as rebound tenderness, as well as imaging showing free air in the abdomen. Bevacizumab (aka avastin) is an antineoplastic recombinant monoclonal antibody that inhibits angiogenesis in a variety of malignancies. Colonic perforation is a recognised but rare complication of this therapy, likely due to aforementioned bowel ischaemia or compromised mucosal microcirculation which increases susceptibility to injury. We are presenting a case of an unrecognised bowel perforation caused in a patient with abdominal carcinomatosis.